Necrotizing Soft Tissue Infection of the Breast during COVID-19 Pandemic - Nadia Kamagate; Robert DeVito (Case Reports in Surgery)
Necrotizing soft tissue infection has been historically recognized as a severe, rapidly spreading soft tissue infection associated with a very high risk of mortality. Cases of primary necrotizing fasciitis of the breast are rarely described but often fatal. We present a case of necrotizing soft tissue infection of the right breast extending to the anterior abdominal wall in a 39-year-old obese female, with a history of tobacco use. The patient presented 10 days after symptom onset due to concerns and anxiety related to COVID-19 exposure. This delay allowed for further extension and smoldering of the breast infection. The treatment of this aggressive disease process begins with early diagnosis, where a high index of suspicion is vital. Once diagnosed, the treatment regimen should be composed of emergent surgical debridement, which can include breast salvage debridement or total mastectomy, in addition to antibiotic therapy.